2009
DOI: 10.1111/j.1476-5381.2009.00471.x
|View full text |Cite|
|
Sign up to set email alerts
|

U‐shaped dose‐dependent effects of BmK AS, a unique scorpion polypeptide toxin, on voltage‐gated sodium channels

Abstract: Background and purpose: Buthus martensi Karsch (BmK) AS is a scorpion polypeptide toxin, said to target the voltage-gated sodium channels (VGSCs). However, the mechanism of action of BmK AS on the VGSCs has yet to be defined. Experimental approach: We examined the electrophysiological effects of BmK AS in a wide dose range on the rat brain-type VGSC a-subunit, rNav1.2a, heterologously expressed in Xenopus oocytes and on the VGSCs endogenously expressed in the dorsal root ganglion neuroblastoma ND7-23 cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 21 publications
0
21
1
Order By: Relevance
“…In the Xenopus oocytes, BmK AS depolarized the voltage dependence of activation and inactivation of Na v 1.2 at 0.1 and 500 nM whereas hyperpolarized them at 1 nM. In the ND7-23 cells, BmK AS hyperpolarized the voltage dependence of activation and inactivation at 0.1, 1 and 100 nM but not 10 nM (Zhu et al 2009). This unique U-shaped dose-dependent modulation pattern of BmK AS could also be observed for Na v 1.3 (Liu et al 2012).…”
Section: Pharmacological and Molecular Mechanisms Of Bmk Toxins Intermentioning
confidence: 87%
“…In the Xenopus oocytes, BmK AS depolarized the voltage dependence of activation and inactivation of Na v 1.2 at 0.1 and 500 nM whereas hyperpolarized them at 1 nM. In the ND7-23 cells, BmK AS hyperpolarized the voltage dependence of activation and inactivation at 0.1, 1 and 100 nM but not 10 nM (Zhu et al 2009). This unique U-shaped dose-dependent modulation pattern of BmK AS could also be observed for Na v 1.3 (Liu et al 2012).…”
Section: Pharmacological and Molecular Mechanisms Of Bmk Toxins Intermentioning
confidence: 87%
“…Based on the previous pharmacological studies of BmK AS on sodium channels, it was concluded that the voltage-dependent activation and inactivation of these VGSC subtypes displayed a U-shaped shift in response to different concentration of BmK AS (0.1, 1, 10, 50, 100, 500 nM)1416. In the current research, three of the concentrations of BmK AS (1, 10 and 100 nM) were chosen to investigate the pharmacological characteristics of BmK AS on Na v 1.2α with or without β1 subunit.…”
Section: Discussionmentioning
confidence: 99%
“…BmK AS was found to stimulate noradrenaline release from rat hippocampus slices by augmentation of sodium influx13. Electrophysiological studies also demonstrated that BmK AS could depolarized the voltage-dependence of fast or slow inactivation, resulting in slower inactivation14.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…BmK neurotoxins targeting membrane channels such as voltage-gated Na + channels (VGSCs) and K + channels are the prime suspects [19][20][21][22][23][24][25] . BmK I, a toxin specific to VGSC receptor site 3, increases Na + currents and delays the inactivation of VGSCs [26] .…”
Section: Variousmentioning
confidence: 99%